The Neurokinin-1 Receptor Contributes to the Early Phase of Lipopolysaccharide-Induced Fever via Stimulation of Peripheral Cyclooxygenase-2 Protein Expression in Mice - Pakai, Eszter; Tekus, Valeria; Zsiboras, Csaba; Rumbus, Zoltan; Olah, Emoke; Keringer, Patrik; Khidhir, Nora; Matics, Robert; Deres, Laszlo; Ordog, Katalin; Szentes, Nikolett; Pohoczky, Krisztina; et al. (Frontiers in Immunology, 2018)
Neurokinin (NK) signaling is involved in various inflammatory processes. A common manifestation of systemic inflammation is fever, which is usually induced in animal models with the administration of bacterial lipopolysaccharide (LPS). A role for the NK1 receptor was shown in LPS-induced fever, but the underlying mechanisms of how the NK1 receptor contributes to febrile response, especially in the early phase, have remained unknown. We administered LPS (120 µg/kg, intraperitoneally) to mice with the Tacr1 gene, i.e., the gene encoding the NK1 receptor, either present (Tacr1+/+) or absent (Tacr1-/-) and measured their thermoregulatory responses, serum cytokine levels, tissue cyclooxygenase-2 (COX-2) expression, and prostaglandin E2 concentration. We found that the LPS-induced febrile response was attenuated in Tacr1-/- compared to their Tacr1+/+ littermates starting from 40 min postinfusion. The febrigenic effect of intracerebroventricularly administered prostaglandin E2 was not suppressed in the Tacr1-/- mice. Serum concentration of pyrogenic cytokines did not differ between Tacr1-/- and Tacr1+/+ at 40 min post-LPS infusion. Administration of LPS resulted in amplification of COX-2 mRNA expression in the lungs, liver, and brain of the mice, which was statistically indistinguishable between the genotypes. In contrast, the LPS-induced augmentation of COX-2 protein expression was attenuated in the lungs and tended to be suppressed in the liver of Tacr1-/- mice compared with Tacr1+/+ mice. The Tacr1+/+ mice responded to LPS with a significant surge of prostaglandin E2 production in the lungs, whereas Tacr1-/- mice did not. In conclusion, the NK1 receptor is necessary for normal fever genesis. Our results suggest that the NK1 receptor contributes to the early phase of LPS-induced fever by enhancing COX-2 protein expression in the periphery. These findings advance the understanding of the crosstalk between NK signaling and the “cytokine-COX-2- prostaglandin E2” axis in systemic inflammation, thereby open up the possibilities for new therapeutic approaches.